2010
DOI: 10.1016/j.toxlet.2008.12.018
|View full text |Cite
|
Sign up to set email alerts
|

Urinary profiles to assess polycyclic aromatic hydrocarbons exposure in coke-oven workers

Abstract: Aim of the study was the assessment of exposure of coke-oven workers to polycyclic aromatic hydrocarbons (PAHs) by determination of urinary profiles of hydroxylated and unmetabolized PAHs. Fifty-five Polish coke-oven workers were investigated by measurement of 12 hydroxylated metabolites of PAHs (OHPAHs) (1-, 2-hydroxynaphthalene; 2-, 9-hydroxyfluorene; 1-, 2-, 3-, 4-, 9-hydroxyphenanthrene; 1-hydroxyypyrene, 6-hydroxychrysene and 3-hydroxybenzo[a]pyrene) and 13 unmetabolized PAHs (U-PAHs) (from naphthalene to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
31
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 70 publications
(37 citation statements)
references
References 21 publications
4
31
2
Order By: Relevance
“…1-OHP contributed over 28% and 49% to the ∑OH-PAHs in the urine samples from the workers and farmers, suggesting a high potential risk of carcinogenic PAH exposure for the farmers. These results contrast with an exposure characterization study with coke oven workers in Europe, which found that naphthols contributed 59% to the ∑OH-PAHs, followed by hydroxyfluorenes (24%), phenanthrols (9.4%), and 1-OHP (7.3%) (Campo et al, 2010).…”
Section: Urinary Pahs and Bt Levels And Their Relationships With Biomcontrasting
confidence: 97%
“…1-OHP contributed over 28% and 49% to the ∑OH-PAHs in the urine samples from the workers and farmers, suggesting a high potential risk of carcinogenic PAH exposure for the farmers. These results contrast with an exposure characterization study with coke oven workers in Europe, which found that naphthols contributed 59% to the ∑OH-PAHs, followed by hydroxyfluorenes (24%), phenanthrols (9.4%), and 1-OHP (7.3%) (Campo et al, 2010).…”
Section: Urinary Pahs and Bt Levels And Their Relationships With Biomcontrasting
confidence: 97%
“…Hydroxy and dihydroxy-PAHs are excreted from the body with urine in the form of glucuronides and sulfates (Jacob and Seidel, 2002). Parent PAHs are not completely metabolized to OH-PAHs in the human body, therefore, urine contains a mixture of both PAHs and OH-PAHs (Becher and Bjorseth, 1983; Campo et al, 2006; Campo et al, 2007; Campo et al, 2010). …”
Section: Introductionmentioning
confidence: 99%
“…Many PAHs have been detected in urine from urban populations exposed to air pollutants (Campo et al, 2007, 2009, 2011; Serdar et al, 2003; Sobus et al, 2008b; Waidyanatha et al, 2003) as well as from workers exposed to emissions containing PAHs (Campo et al, 2007, 2009, 2010, 2011; Rossella et al, 2009; Serdar et al, 2003; Sobus et al, 2008b, 2009b; Waidyanatha et al, 2003). Given the abundance of volatile PAHs in DE, we hypothesized that urinary levels of gas-phase PAHs would elevate upon short-term exposure to air concentrations of DE that were well above ambient values.…”
Section: Introductionmentioning
confidence: 99%